Analisa Sambungan Lentur Antar Dua Gedung Beton Bertulang - Dewi Purnama Sari; Muhammad Fitrah; Andrisman Satria (Universitas Teuku Umar, 2021)
Indonesia is in the three tectonik yaitu Indo-Australia, Eurasia dan Pacific may be Indonesia have disaster of earthquake. Aceh Barat is in the a town in Indonesia include in to region 5. However, a bulding must have resistance for earthquake. In this research investigate influence warp connection depend on deformation and bending moment caused by earthquake. Investigation of spectrum response do to variation model of wrap connection in distance 15 cm for Model A, the structure without wrap connection for Model B,the structure with wrap connection in distance 30 cm for Model C, the structure without wrap connection in distance 30 mm for Model D and the structure without wrap connection exactly for Model E. The analysis by SAP 2000 Software to find out the bending moment and deformation. The result moment and deformation consequtively are Model A is 49,37 KNm and 12,623 mm, Model B is 59,88 KNm and 15,395 mm, Model C is 50,33 KNm and 12,814 mm, and Model D is 59,88 KNm and 15,395 mm, Model E is 43,84 KNm and 12,268 mm. Using wrap connection have moment and deformation smaller than the model without wrap connection that the large distance. According to that result, wrap connection can solve the problem to the impact between two building. Keywords—Earthquake, SAP 2000 Software, wrap connection, deformation, impact